STUDI DESKRIPTIF MANAJEMEN PENDIDIKAN INKLUSIF DI SMA - Hasanah Ramli, Nurul (Jurnal Pendidikan Khusus, 2018)
ABSTRACT  Inclusive education is the provision of education system that provides opportunities for all children with special needs or gifted talented to get the same education with another regular students and respect diversity, and without discrimination for all students. Through inclusive education, students with special needs can follow education or learning in the educational environment together with the regular students. The purpose of this study was to describe the management of inclusive education at Public Senior High School 10 Surabaya. This research used descriptive method with qualitative approach. Data collection techniques are obtained  through observation, interviews and documentation. In the  data analysis techniques used several steps including: the data condensation, data display (presentation of data), conclusion and verification. The conclusions of this study were: 1 ) student management includes enrollment, all students with special needs have equal opportunity but with a note must have intelligence above minety (90), in accordance with the number of available quota as well as consideration of resources owned ( 2) curriculum management using a flexible and modifiable 2013 curriculum (3), 3) management of teachers and education personnel, must have specific criteria competent in their field, 4) classroom management and learning using class setting: inclusive with full regular classes; 5) management of facilities and infrastructure for learning media, accessible school infrastructure for students with special needs and environmentally friendly for regular students; 6) funding management of government, parents, and community participation 7) relations of society and school there was school committees and cooperation with universities.   Keywords: management, inclusive education